Analysis of Arabic Reading Skills at Modern Islamic Boarding School Arafah Sungai Penuh, in The 12th Grade Of Aliyah : Analisis Kemampuan Membaca Bahasa Arab di Pondok Pesantren Modern Arafah Sungai Penuh, pada Kelas XII Aliyah - Sindi Febria Fitri; Musdizal (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
Reading and understanding Arabic is crucial as it facilitates comprehension of texts, improves communication, and enhances reading skills. In Arabic, reading skills are known as